Transcription factors ETF, E2F, and SP-1 are involved in cytokine-independent proliferation of murine hepatocytes - Zellmer, Sebastian; Schmidt-Heck, Wolfgang; Godoy, Patricio; Weng, Honglei; Meyer, Christoph; Lehmann, Thomas; Sparna, Titus; Schormann, Wiebke; Hammad, Seddik; Kreutz, Clemens; Timmer, Jens; Weizsäcker, Fritz von; et al. (Hepatology, 2010)
The cellular basis of liver regeneration has been intensely investigated for many years. However, the mechanisms initiating hepatocyte “plasticity” and priming for proliferation are not yet fully clear. We investigated alterations in gene expression patterns during the first 72 hours of C57BL/6N mouse hepatocyte culture on collagen monolayers (CM), which display a high basal frequency of proliferation in the absence of cytokines. Although many metabolic genes were down-regulated, genes related to mitogen-activated protein kinase (MAPK) signaling and cell cycle were up-regulated. The latter genes showed an overrepresentation of transcription factor binding sites (TFBS) for ETF (TEA domain family member 2), E2F1 (E2F transcription factor 1), and SP-1 (Sp1 transcription factor) (P < 0.001), all depending on MAPK signaling. Time-dependent increase of ERK1/2 phosphorylation occurred during the first 48 hours (and beyond) in the absence of cytokines, accompanied by an enhanced bromodeoxyuridine labeling index of 20%. The MEK inhibitor PD98059 blunted these effects indicating MAPK signaling as major trigger for this cytokine-independent proliferative response. In line with these in vitro findings, liver tissue of mice challenged with CCl4 displayed hepatocytes with intense p-ERK1/2 staining and nuclear SP-1 and E2F1 expression. Furthermore, differentially expressed genes in mice after partial hepatectomy contained overrepresented TFBS for ETF, E2F1, and SP-1 and displayed increased expression of E2F1. Conclusion: Cultivation of murine hepatocytes on CM primes cells for proliferation through cytokine-independent activation of MAPK signaling. The transcription factors ETF, E2F1, and SP-1 seem to play a pronounced role in mediating proliferation-dependent differential gene expression. Similar events, but on a shorter time-scale, occur very early after liver damage in vivo. (HEPATOLOGY 2010;.)
First published: 20 August 2010
Gesehen am 10.04.2024